Perancangan Sistem Monitoring Kinerja Panel Surya untuk Tambak Udang berbasis IoT - Handoko Catur Rakhmad; Imam Sutrisno; Ari Wibawa Budi Santosa; Heri Sutanto (CV. Creative Tugu Pena, 2025)
Internet of Things (IoT)-based monitoring systems are increasingly being adopted across various sectors, including aquaculture. Shrimp farming, in particular, relies on a stable energy supply to operate aeration and water circulation systems. Solar panels offer an efficient renewable energy solution; however, their optimal performance requires continuous and reliable monitoring. This study aims to design and implement an IoT-based monitoring system to track solar panel performance in shrimp farms, thereby enhancing energy utilization efficiency. The system integrates sensors for current, voltage, temperature, and light intensity with a microcontroller and an IoT platform for real-time data acquisition and analysis. The test results demonstrate that the system effectively provides accurate and timely information on solar panel performance, enabling early detection of efficiency losses and prompt maintenance actions. The implementation of this system is expected to increase energy resilience and operational efficiency in shrimp farming operations. By combining IoT technology with renewable energy monitoring, this research offers a practical and scalable solution tailored for remote aquaculture environments. Additionally, the study highlights the feasibility of using low-cost hardware and open-source platforms, making the system accessible for broader application, particularly in developing regions. This contribution supports the advancement of sustainable and energy-efficient aquaculture practices through innovative, technology-driven approaches.